Preliminary phytochemical screening and evaluation of hypoglycemic properties of the root extract of Uveria chamae (Bangladesh Journal of Pharmacology, 2015)
The purpose of this study is to evaluate the hypoglycaemic properties and preliminary phytochemical screening of Uveria chamae. The hypoglycaemic properties of Uveria chamae was assessed on normoglycaemic rat that received single dose of the extract at 250 and 500 mg/kg body weight and blood glucose levels estimated at 2, 4, and 6 hours (single dose study). The hypoglycaemic property of the extract was also evaluated in normoglycemic rats by oral glucose tolerance test. Phytochemical screening of the extract for the presence of secondary metabolites was performed with standard methods. The extract showed a significant (p